PERISTILAHAN DALAM ADAT PERKAWINAN MASYARAKAT MELAYU PONTIANAK - Aminah, Syarifah; Muzammil,, Ahmad Rabi ul; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe terminology in the marriage tradition of the Pontianak Malay community was carried out aimed at preserving knowledge about terms in culture. The problem in this study is how to describe the procession of traditional marriage in Pontianak Malay community in Batulayang Village from the pre-marital stage of the marriage to the post-marital period; what is the term lingual terminology in the Pontianak Malay community customary marriage in Batulayang Village; what is the meaning of terminology in Pontianak Malay community marriage in Batulayang Village. The method in this research is descriptive qualitative. Descriptive form is a description of the customary marriage of the Pontianak Malay community in a qualitative form, namely an explanation in the form of words and sentences. Based on the analysis of the data the researcher draws conclusions that there are 76 terms in the customary marriage of the Pontianak Malay community in the Batulayang Village. The most data is found in endocentric phrases in the form of tools and materials, which are 33 leksemes. The least amount of data in the form of the word affixation (affix), there is one lexeme and no data at all, namely infix. Keywords: Traditional Marriage, Pontianak Malay, Terminology, Lingual Form, and Meaning